The cost of peace without rights. Displaced persons/returnees in Kosovo and Bosnia and Herzegovia - Jara Gómez, Ana M. (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2022)
Kosovo and Bosnia Herzegovina are entirely different countries and at the same time similar in terms of the situation of returnees after armed conflicts. Both are relevant because of the large number of people who were displaced, because of the ethnic dimension of the displacements and because the political changes produced after the conflicts are so far-reaching that they reshaped the map of Europe. It is a commonplace to affirm that social and political interculturalism is tantamount to tolerance and social peace, especially in post-war periods, when it is essential to speak of reconciliation in order to ensure that a return to normality is possible. This article seeks to question, at least as a self-evident and universal truth, the unreserved virtue of interculturality imposed in the immediate aftermath of violent conflict. In these contexts, greater importance must be given to the ethnic groups that have been left on the margins of exclusion. In Bosnia-Herzegovina and Kosovo, the collapse of communism, political changes and conflicts have had enormous socio-economic consequences on Roma ethnicities.
Keywords: returnees; ethnic identity; displacement